2020
DOI: 10.1016/j.rbmo.2020.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Physical resolution of tubal ectopic pregnancy on ultrasound imaging following successful expectant management

Abstract: What is the time required for complete physical resolution of tubal ectopic pregnancies diagnosed on ultrasound imaging in women undergoing successful expectant management? DesignA prospective observational cohort study of 177 women who had successful expectant management of tubal ectopic pregnancy, who attended a single Early Pregnancy Unit between January 2014 and Downloaded for Anonymous User (n/a) at University College London Hospitals NHS Foundation 2020. For personal use only. No other uses without permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Two studies were excluded as they were not RCTs. Four studies were excluded as the comparison was inappropriate: three of these included prostaglandins as part of the medical management and the other compared placebo to oral methotrexate, which is not considered a viable treatment strategy ( Elson et al , 2016 ; American College of Obstetrics and Gynecology (ACOG), 2018). Two studies were not included as they were unfinished studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies were excluded as they were not RCTs. Four studies were excluded as the comparison was inappropriate: three of these included prostaglandins as part of the medical management and the other compared placebo to oral methotrexate, which is not considered a viable treatment strategy ( Elson et al , 2016 ; American College of Obstetrics and Gynecology (ACOG), 2018). Two studies were not included as they were unfinished studies.…”
Section: Resultsmentioning
confidence: 99%
“…A further potential advantage of EM is that there is the possibility to attempt to conceive again more quickly than patients treated with methotrexate, who are advised to wait 3 months ( Elson et al , 2016 ). However, a recent prospective observational cohort study found that in 5% of patients with tubal EP managed expectantly, it took longer than 3 months for the physical resolution on transvaginal ultrasonography after the β-hCG had normalised ( Dooley et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on MTX noted a higher treatment success with lower hCG levels. 20,[24][25][26][27] Similarly, studies on expectant management favor a lower hCG for successful resolution, 6,14,22,23,28 with the subgroup of women with initial hCG <1500 IU/L having a 77% success rate. 8 Our mean time to resolution of 19.7 days with MTX and 21.2 days with expectant management was similar to that of other studies.…”
Section: Ta B L E 5 Combined Outcomesmentioning
confidence: 99%
“…Improvements in diagnostic ultrasound have resulted in the detection of small failing tubal ectopic pregnancies, which can be managed successfully expectantly, with appropriate case selection [1][2][3][4] . We report a case of pseudoaneurysm complicating expectant management of a tubal ectopic pregnancy.…”
Section: Pseudoaneurysm Complicating Expectantly Managed Tubal Ectopi...mentioning
confidence: 99%